The Theory of Effort Minimization in Physical Activity. Issue 3 (July 2021) - Cheval, Boris; Boisgontier, Matthieu P.
Abstract : Although the automatic attraction to effort minimization has been evidenced in multiple fields, its potential role in explaining the pandemic of physical inactivity has been overlooked. The theory of effort minimization in physical activity (TEMPA) fills this gap. TEMPA seeks to obtain a more accurate understanding of the neuropsychological determinants of movement-based behaviors. Abstract : We put forward a theoretical framework aiming to develop a more accurate understanding of the neuropsychological determinants of physical activity.